EFEK GENETIK IRADIASI SINAR GAMMA PADA LALAT BUAH (Drosophila melanogaster Meig) JANTAN PRA KAWIN - Sofyan, Rochestri; Sumpena, Yana; Syarif, Supartini; R, Ira Adiyati (BERITA BIOLOGI, 2007)
An investigation about the effect of gamma irradiation on the progeny development of male fruit fly (Drosophila melanogaster Meig) pre-marital has been done.The purpose of this study is to comprehend the changes in progeny as well as the probability of abnormal phenotype to fruit fly progeny as the result of gamma irradiation to male fruit fly pre-marital.The study has been conducted using Completely Randomize Design method with six repetitions. Pre-marital male fruit flies were irradiated at the doses of 10, 15 and 20 Gy with gamma ray from "Co source, having a dose rate of 0.66 Gy/hour. The irradiated fruit flies and non-irradiated ones as control, mated immediately with virgin female, then the first progeny (F,) was observed. The parameters used in this study were the total number of progeny and the number of abnormal phenotype of the progeny. The data were analyzed by using Analysis of varians (ANOVA), proceeded with Duncan test. Regression analyses was also perform to comprehend how far gamma irradiation affected the fruit fly progeny. The result indicated that gamma irradiation significantly affected (a=l%) the total number of progeny The average total number of fruit fly progeny caused by gamma irradiation with the doses of 10, 15 and 20 Gy, tend to decrease i.e. 43, 81 and 85%. It appeared that gamma irradiation caused mutation which figures as wing abnormality. It was also found that an irradiation dose of 10 Gy do not caused abnormality. Abnormal phenotype to the wing organ began to appear at the given dose of 15 Gy.